NMR metabolite profiles of dairy: A review. (March 2019) - Scano, Paola; Cusano, Erica; Caboni, Pierluigi; Consonni, Roberto
Abstract: Nuclear magnetic resonance (NMR) spectroscopy, which is one of the most powerful "omics" analytical platforms, has been broadly adopted recently in foodomics. 1 H NMR has been applied to the study of the metabolite profile of dairy products throughout the supply chain, in relation to different aspects such as animal health, milk quality, geographical origin and cheese ripening process. This review reports and discusses the literature on the topic, also collecting the identified metabolites in a descriptive table and depicting them in a Venn diagram for both milk and cheese; moreover, experimental details of the reviewed papers have been reported. The present review provides an exhaustive state-of-the-art in the field of dairy products, addressing both NMR experts and non-experts to the still unexplored potential applications of NMR in dairy characterisation, and in general in foodomics.